2017
DOI: 10.1590/1678-457x.14016
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of synbiotic yogurts with yacon pulp (Smallanthus sonchifolius) and assessment of the viability of lactic acid bacteria

Abstract: The aim of this study was check the effects of sugar, yacon pulp and skimmed milk powder in the aroma, flavour, texture, appearance, overall impression and intent to purchase on synbiotic yogurts to optimize the formulation using Response Surface Methodology. The most accepted formulations were subjected to viability tests during 21 days by counting traditional and probiotic bacteria. Were constructed a complete 2 3 factorial design, totalling 17 experiments, and considered independent variables (percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Scher et al (2009) observed that the inulin content decreased significantly after 'yacon' drying, and they concluded that such a decrease could be due to its hydrolysis, improved by these conditions. As previously mentioned, this degradation is undesirable since fructan presents a wide range of functional properties (Padilha et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scher et al (2009) observed that the inulin content decreased significantly after 'yacon' drying, and they concluded that such a decrease could be due to its hydrolysis, improved by these conditions. As previously mentioned, this degradation is undesirable since fructan presents a wide range of functional properties (Padilha et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in the fructan concentration was expected in all the treatments once fructan oxidation occurs due to the exposure to light and heat, with the FR ranging from 16.84 to 37.72%. Such fructan losses in osmotic experiments (OD -VD and OD -CD) are related to the natural leaching flux that occurs in osmotic processes once this saccharide possesses a hydrophilic nature and migrate from the internal tissue to the osmotic media (Oliveira et al, 2016;Padilha et al, 2017).…”
Section: Resultsmentioning
confidence: 99%